An Integrative Model for Developing The Personal Qualities Of Future Teachers Through Historical And Fictional Books - Mavluda Kadirova (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Developing personal qualities in future teachers is a crucial element in preparing them for their professional roles. Historical and fictional books provide rich, multidimensional resources that can enhance empathy, critical thinking, and ethical reasoning. This article explores an integrative pedagogical model that incorporates these literary genres to nurture personal qualities in teacher trainees. The suggested model combines cognitive, emotional, and experiential learning strategies to foster qualities such as responsibility, creativity, and cultural awareness.